IDENTIFICATION OF STUDENTS MENTAL MODEL IN HEAT CONVECTION CONCEPT - Amalia, Rifdah (2016)
This research depended by previous studies that only to find out the misconceptions of students without figuring out the mechanism of the misconceptions. The mechanism of misconceptions can be studied more deeply with mental models. The purpose of this study was to find students 'mental models of heat convection, the relationship between mental model and predictions and the relationship between students mental models and their conceptions category. The method used in this study is exploratory mixed method design that implemented in one of the high schools in Bandung. The results showed that 7 mental models of heat convection in Chiou's study (2013), only first model (diffusion-based convention), third model (evenly distributed convection) and fifth model (warmness topped convection II) were found and model X (hybrid convection) as a new mental model. In addition, no specific relationship between mental models and categories of students' conceptions. And also very complex relationship between mental models and students prediction. At the beginning some students try to run their mental model when making predictions, but they did not survive till the end of the interview process. Similarly, when students are given a new phenomenon, the students have not been able to run their mental models even tend to be fickle.;---Penelitian ini dilatar belakangi oleh penelitian-penelitian sebelumnya yang hanya mencari tahu miskonsepsi siswa tanpa mencari tahu mekanisme terjadinya miskonsepsi. Mekanisme terjadinya miskonsepsi bisa dikaji lebih dalam dengan model mental. Tujuan penelitian ini adalah untuk memperoleh gambaran model mental siswa mengenai konveksi kalor serta hubungan model mental yang diperoleh dengan prediksi siswa dan hubungan model mental dengan kategori konsepsi siswa. Metode penelitian yang digunakan yaitu exploratory mixed method design yang diterapkan di salah satu SMA Negeri di Kota Bandung. Hasil penelitian menunjukkan bahwa dari 7 model mental konveksi kalor yang ditemukan oleh Chiou (2013), hanya model 1 (diffusion based convention), model 3 (evenly distributed convection) dan model 5 (warmness topped convection II) yang ditemukan dan terdapat temuan model mental baru yang peneliti namakan sebagai model X (hybrid convection). Selain itu, tidak ada hubungan yang spesifik antara model mental dan kategori konsepsi siswa. Dan juga terdapat hubungan yang sangat kompleks antara model mental dan prediksi siswa. Meskipun beberapa siswa mencoba untuk menjalankan model mental pada saat membuat prediksi di awal, mereka tidak bertahan dalam menjalankannya hingga proses akhir dari wawancara. Begitu pula ketika siswa diberi fenomena baru, siswa belum bisa menjalankan model mentalnya dengan baik bahkan cenderung berubah-ubah.